1984
DOI: 10.1300/j052v04n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes and Zinc Status of an Elderly Rural Population

Abstract: The zinc status and energy, protein, and zinc intakes of a group of 50 individuals, 65 years of age or older, residing in rural Pennsylvania have been described. Generally, this group was in good zinc status, although zinc intakes were considerably less than the RDA for most individuals. Energy intakes were generally adequate and protein intakes more than sufficient. It would appear possible to maintain adequate zinc status (as assessed by plasma and hair zinc determinations) with zinc intakes of less than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…B. K. Lewis et al Schraibman & Stratton (1985) also found reduced serum zinc levels in elderly patients with leg ulceration and it has been suggested that the local demands of healing may expose an otherwise marginal zinc deficiency (Senapati 8 Thompson, 1985). Within an apparently healthy elderly pop ulation zinc status may be maintained when zinc intake is low providing energy and protein intakes are adequate (Fosmire et al, 1984). Being house-bound may compromise zinc status in elderly patients and inactivity may result in loss of zinc from lean body tissue (Bunker 8 Clayton, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…B. K. Lewis et al Schraibman & Stratton (1985) also found reduced serum zinc levels in elderly patients with leg ulceration and it has been suggested that the local demands of healing may expose an otherwise marginal zinc deficiency (Senapati 8 Thompson, 1985). Within an apparently healthy elderly pop ulation zinc status may be maintained when zinc intake is low providing energy and protein intakes are adequate (Fosmire et al, 1984). Being house-bound may compromise zinc status in elderly patients and inactivity may result in loss of zinc from lean body tissue (Bunker 8 Clayton, 1989).…”
Section: Introductionmentioning
confidence: 99%